X‐ray diffraction analysis and in vitro characterization of the UAM2 protein from Oryza sativa. Issue 4 (1st April 2017) - Welner, Ditte Hededam; Tsai, Alex Yi-Lin; DeGiovanni, Andy M.; Scheller, Henrik Vibe; Adams, Paul D.
Abstract : The UAM2 protein from O. sativa was cloned, expressed, purified and crystallized, and a complete data set was obtained from the radiation‐sensitive crystals by low‐dose vector data collection. In addition, it is shown that UAM2 is likely to exist as a monomer in solution and contains at least one intramolecular disulfide bridge or, alternatively, a structural metal ion. Abstract : The role of seemingly non‐enzymatic proteins in complexes interconverting UDP‐arabinopyranose and UDP‐arabinofuranose (UDP‐arabinosemutases; UAMs) in the plant cytosol remains unknown. To shed light on their function, crystallographic and functional studies of the seemingly non‐enzymatic UAM2 protein from Oryza sativa (OsUAM2) were undertaken. Here, X‐ray diffraction data are reported, as well as analysis of the oligomeric state in the crystal and in solution. OsUAM2 crystallizes readily but forms highly radiation‐sensitive crystals with limited diffraction power, requiring careful low‐dose vector data acquisition. Using size‐exclusion chromatography, it is shown that the protein is monomeric in solution. Finally, limited proteolysis was employed to demonstrate DTT‐enhanced proteolytic digestion, indicating the existence of at least one intramolecular disulfide bridge or, alternatively, a requirement for a structural metal ion.